2004
DOI: 10.2535/ofaj.81.45
|View full text |Cite
|
Sign up to set email alerts
|

Branch of Mylohyoid and Lingual Nerves on Submandibular and Submental Triangles

Abstract: Summary: The mylohyoid nerve (MN) displays several branches in the posterior, intermediate, and anterior region of the mylohyoid muscle (MM) as it courses on the internal surface of the mandibular body. Branches in the intermediate region were found in 66% of the cases (272 out of 413 sides). In the submandibular triangle, one or two large branches of the MN communicated with the lingual nerve at submandibular triangle and submental triangle in 1.45% of the cases (6 out of 413 sides). These distributions of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 6 publications
(8 reference statements)
0
12
0
Order By: Relevance
“…The number of nerve branches entering the MM was evidently more than that of the anterior belly of the digastric muscle. Communications between the MN and LN were mainly found between the premolar and molar region of the mandible, which has been shown to occur at a frequency ranging from 45 to 66% (46.3% Kameda & Uber den, 1952; 66% Sato et al, 2004, this study, 63%). It is interesting to point out that the communication occurs between the LN and MN, both of which originate from the mandibular nerve.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The number of nerve branches entering the MM was evidently more than that of the anterior belly of the digastric muscle. Communications between the MN and LN were mainly found between the premolar and molar region of the mandible, which has been shown to occur at a frequency ranging from 45 to 66% (46.3% Kameda & Uber den, 1952; 66% Sato et al, 2004, this study, 63%). It is interesting to point out that the communication occurs between the LN and MN, both of which originate from the mandibular nerve.…”
Section: Discussionmentioning
confidence: 50%
“…The posterior trunk of the MN gives rise to the main sensory nerves, that is, the auriculotemporal, lingual, and inferior alveolar nerves and motor branches to the MM and the anterior belly of the digastric muscle (Brennan, Webb, Kemidi, Spratt, & Standring, 2008). Communication between the MN and LN was also found at some frequency (46.3% Kameda & Uber den, 1952; Sato, Sunohara, Ueno, & Yoshida, 2004, 66%). In dental implant or oral surgery, the inner surface of the mandible has become an important area for lingual flap dental treatment (Urban et al, 2018).…”
Section: Introductionmentioning
confidence: 97%
“…Sato et al reported, in 1.45% of cases, two large communications between the MHN with the LN in submandibular and submental regions. 25 However, Kameda reported 46.3% connection between these nerves. 26 An unusual communication between these nerves also was reported after the LN crossed the mandibular third molar 3 ( Figure 3).…”
Section: Anatomical Anomalies Of the Mhnmentioning
confidence: 99%
“…In these five cases, all of the NMs ran posteromedial to the IAN [22]. Although most unusual connections between the NM and the lingual nerve (LN) have been reported as case reports [32324], Sato et al [25] investigated this anomaly and revealed that in 1.45% of cases (6/413), one or two large branches of the NM connected with the LN in the submandibular or submental triangles. This incidence was significantly different from that reported by Kameda (1952) [26] who identified communicating branch of the LN and NM in the submental triangle in 46.3% of the cases (74/160).…”
Section: Anatomic Variations Of the Nm And The Mylohyoid Groovementioning
confidence: 99%